Investigating the Diversity in Physiological, and Molecular Responses of Wheat (Triticum aestivum L.) Genotypes under Cadmium Stress - Haitham Mokhles Saad Khatlan; Mohammed Hamdan Al-Issawi; Hail Rihan (مجلة ديالى للعلوم الزراعية, 2024)
Heavy metal toxicity is a real threat to the environment, crop productivity, and the health of humans and their animals, especially when the toxicity enters the food chain. This study investigates the effect of cadmium on the physiological and molecular levels of ten introduced wheat genotypes. Genotypes were stressed by cadmium (75 mg.L-1) in comparison with unstressed treatment to highlight their response to the cadmium. The experiment was laid out as a factorial arrangement in RCBD, with three replicates. The genotypes included in this study varied in their response to cadmium stress during the laboratory tests. Notably, genotype G-41 was superior to the rest of the genotypes in terms of seed vigor (18.58), chlorophyll content (8.72 mg.g-1), and carotenoid content (4.87 mg.g-1), while genotype IRAQ had wider epidermis in the root (2.28 µm) and ordinary epidermis cells (3.10 µm). Cadmium boosted some physiological and anatomical traits (e.g., REC, Chlorophyll, carotenoids, length and width of root epidermis cells). However, cadmium concentration caused a deterioration in some anatomical traits, including cortex thickness and the length of the ordinary epidermis cells. Some wheat genotypes showed more resistance to cadmium stress than others, and G-3 was notably affected by cadmium treatment and this was associated with the high PCS1 expression of the enzyme that chelates Cd to the vacuole (39 folds). It can be concluded that cadmium reduced the physiological performances except for some genotypes that showed more tolerance. Those genotypes could therefore be investigated further to assess the accumulation of cadmium in their grains